Construction of Professional Learning Communities: Perception of School Leaders from Chile and Peru - Tafur Puente, Rosa María (2025)
The objective of this study was to analyze the perceptions of school leaders regarding the principles and practices that guide the construction and development of Professional Learning Communities (PLCs) in schools in Chile and Peru. A qualitative methodology with a descriptive scope was employed. Six school leaders were intentionally selected to participate. Data collection was conducted through focus groups, and the analysis was carried out using grounded theory. The results indicate that participants emphasize pedagogical and distributed leadership as key factors in consolidating PLCs, fostering collaboration and critical reflection on teaching practices. It is concluded that PLCs are fundamental in creating collaborative cultures that enhance educational quality, provided that a shared vision of learning is established.